Reduced prepulse inhibition as a biomarker of schizophrenia (2016)
The startle response is composed by a set of reflex behaviors intended to prepare the organism to face a potentially relevant stimulus. This response can be modulated by several factors as, for example, repeated presentations of the stimulus (startle habituation), or by previous presentation of a weak stimulus (Prepulse Inhibition [PPI]). Both phenomena appear disrupted in schizophrenia that is thought to reflect an alteration in dopaminergic and glutamatergic neurotransmission. In this paper we analyze whether the reported deficits are indicating a transient effect restricted to the acute phase of the disease, or if it reflects a more general biomarker or endophenotype of the disorder. To this end, we measured startle responses in the same set of thirteen schizophrenia patients with a cross-sectional design at two periods: 5 days after hospital admission and 3 months after discharge. The results showed that both startle habituation and PPI were impaired in the schizophrenia patients at the acute stage as compared to a control group composed by 13 healthy participants, and that PPI but not startle habituation remained disrupted when registered 3 months after the discharge. These data point to the consideration of PPI, but not startle habituation, as a schizophrenia biomarker.